2017
DOI: 10.7575/aiac.alls.v.8n.2p.190
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-Assisted Vocabulary Learning: A Review Study

Abstract: Mobile phones are becoming more acceptable toolkits to learn languages. One aspect of English language which has been subject to investigation in mobile assisted language learning (MALL) is vocabulary. This study reviewed some of the studies conducted in various contexts on the effect of MALL on vocabulary learning. We investigated some of the most prominent databases such as Science Direct, Wiley, Scopus and Oxford to find these studies; believing that this study can have pedagogical implications for future r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…They are also the most analysed by research (Afzali et al, 2017). Afzali et al (2017) reiterated another meta-analysis through indexing bases such as Science Direct, Wiley, and Scopus and found that data from several countries confirm that learning other languages and respective vocabularies has greater gains with digital inputs (from the MALL method) than with physical inputs (flashcards, for example). One of the biggest limitations of these studies is the use of English as the MALL's target language.…”
Section: Contact and Working Hours: Flipped Classroom Approachmentioning
confidence: 99%
“…They are also the most analysed by research (Afzali et al, 2017). Afzali et al (2017) reiterated another meta-analysis through indexing bases such as Science Direct, Wiley, and Scopus and found that data from several countries confirm that learning other languages and respective vocabularies has greater gains with digital inputs (from the MALL method) than with physical inputs (flashcards, for example). One of the biggest limitations of these studies is the use of English as the MALL's target language.…”
Section: Contact and Working Hours: Flipped Classroom Approachmentioning
confidence: 99%
“…In other words, it can let users determine their own learning goals, select what they want to learn and assess their progress by themselves. Second, mobile learning apps can provide users immediate feedback (Afzali et al, 2017). Immediate feedback plays an important role in language learning as it can help language learners correct their mistakes and lead learners to the right way.…”
Section: Introductionmentioning
confidence: 99%
“…The term 'Mobile Assisted Language Learning' (MALL) was first introduced by Chinnery (2006) who believed that portable devices can be successfully employed in language learning contexts. Therefore, there is a growing interest in the use of mobile phones to learn EFL in varied contexts and among different age groups (Afzali, Shabani, Basir & Ramazani, 2017;Pérez-Paredes & Zhang, 2022). MALL refers to the availability of learning opportunities wherever and whenever a learner wishes to with the help of mobile devices (Geddes, 2004).…”
Section: Introductionmentioning
confidence: 99%